Development of Biology E-Module Based on POGIL in Virus and Bacteria Material to Train HOTS X Graders of Senior High School - Ningsih, Ani Widia; Hidayatullah, Ahmad Fauzan; Rofi’ah, Ndzani Latifatur (Bioeduca : Journal of Biology Education, 2023)
Higher-Order Thinking Skill (HOTS) is a skill that every individual needs to be able to solve problems quickly, critically, and logically. The condition of HOTS in Indonesia is still low. This study aims to create and assess the feasibility of E-module biology based on POGIL on viral and bacterial materials. This study uses the 4D development model (Define, Design, Develop, and Disseminate but is limited to the Development stage. The product trial sample on 42 science students of grade X was taken randomly. The validation results from media experts, POGIL experts, material experts, HOTS experts, and biology teachers, namely, 83.3%, 85%, 82.5%, 86.2%, and 88.6%. The overall results from the expert validation are of very decent quality. The student's responses regarding the E-module based on POGIL on the virus and bacteria material obtained a mark of 85.3%, which included the very decent category. E-module is a feasible type to be applied as a learning resource for X senior high school grades.